1981
DOI: 10.1126/science.212.4498.1038
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Substance of Mytilus edulis : Novel Adhesive Containing L-Dopa and Hydroxyproline

Abstract: The fouling marine mussel Mytilus edulis attaches itself to various substrates by spinning byssal threads, the adhesive discs of which are rich in the amino acid 3,4-dihydroxyphenylalanine (dopa). An acid-soluble protein was extracted and purified from the phenol gland located in the byssus-secreting foot of the animal. This protein is highly basic and contains large amounts of lysine, dopa, and 3- and 4-hydroxyproline. The composition of this protein and its sticky tendencies in vitro strongly suggest that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
666
1
5

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 967 publications
(695 citation statements)
references
References 23 publications
(6 reference statements)
3
666
1
5
Order By: Relevance
“…1e). [13][14][15] DOPA demonstrates high affinity for chemically distinct substrates via covalent or noncovalent interactions. Dopamine contains both side chain functionalities of DOPA and lysine, which resembles mussel adhesive proteins (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1e). [13][14][15] DOPA demonstrates high affinity for chemically distinct substrates via covalent or noncovalent interactions. Dopamine contains both side chain functionalities of DOPA and lysine, which resembles mussel adhesive proteins (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Excess of the surface modifying ligands were removed from the isolated nanoparticles by repeated dialysis. dl-DOPA is a derivative of phenylalanine and abundantly present in the mussel adhesive protein Mytilus edulis, [41] and considered to have high affinity binding group to stabilize iron oxide nanoparticles in water [42] and physiologic buffers via M-O (M = Fe, Mn) bonding [43], [44], [45] and [46]. In addition dl-DOPA can provide the opportunity of conjugating DOTA on the surface of the nanoparticles through amide bond formation.…”
Section: Crystal Structure and Morphology Of The Nanoparticlesmentioning
confidence: 99%
“…Hydroxylation (e.g., tyrosine to DOPA) and phosphorylation (e.g., serine to phosphoserine) are post‐translational modifications commonly used by marine organisms to modify the adhesive properties of their cement proteins 7, 8, 27, 28, 29. As previously mentioned, barnacle cement does not contain DOPA;10, 11, 12 however, Gohad et al and Dickinson et al demonstrated that cyprid cement and the barnacle cementing apparatus are phosphorylated, respectively 14, 30.…”
mentioning
confidence: 99%